Effect of Nitrogen and Molybdenum on Post Harvest Soil Characteristics and Economic Yield of Bush Bean (Phaseolus vulgaris L.). - Hossain, MK; Islam, MS (The Agriculturists, 2010)
A field experiment was carried out at the research field of Sher-e-Bangla Agricultural University, Dhaka during December 2006 to February 2007 to study the effect of nitrogen and molybdenum on post harvest soil characteristics and economic yield of bush bean (Phaseolus vulgaris L.). The treatments consisted of 5 levels of N (0, 40, 80, 120 and 160 kg ha-1) designated and 3 levels of Mo (0, 0.5 and 1.0 kg ha-1). Urea and ammonium molybdate were used as the sources of nitrogen and molybdenum, respectively. The characteristics of the post harvest soils showed a marked variation in relation to soil pH, soil organic carbon, N, P, K and S content in the post harvest soil due to application of N and Mo. The highest organic carbon (0.60%) and total N (0.072%) was obtained from N120. The highest organic carbon (0.60%) and total N (0.068%) was obtained from Mo0.5. The maximum organic carbon was obtained (0.63%) from N120Mo0.5 treatment combination. The maximum total N was obtained (0.075%) from N160Mo0.5 treatment combination. The results of economic analysis showed that the highest net benefit of Tk.1,68,722.00 ha-1 was obtained in N120Mo0.5 treatment and the lowest net benefit of Tk.16,559.00 ha-1 was found in control.